Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1111/jan.14326
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of a nurse‐led intervention to support family caregivers in end‐of‐life care: Study protocol for a cluster randomized controlled trial

Abstract: Aim To evaluate the feasibility of a structured nurse‐led supportive intervention and its effects on family caregivers in end‐of‐life care at home. Background Family caregivers are crucial in end‐of‐life care. They may experience burden due to the responsibilities associated with caregiving. Some family caregivers feel insufficiently prepared for their caregiver role. Nurses have a unique position to provide supportive interventions at home to reduce caregivers’ burden and improve preparedness. However, few nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Since the caregiver’s role is an important element in ensuring the well-being of the person being cared for [ 11 ], intervention in this population group becomes a priority. There are intervention and/or support programs that have been positively evaluated [ 12 - 15 ], although most of them are based on in-person training. However, research has shown that many caregivers underutilize the supports available to them and instead try to handle everything by themselves [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since the caregiver’s role is an important element in ensuring the well-being of the person being cared for [ 11 ], intervention in this population group becomes a priority. There are intervention and/or support programs that have been positively evaluated [ 12 - 15 ], although most of them are based on in-person training. However, research has shown that many caregivers underutilize the supports available to them and instead try to handle everything by themselves [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Support for caregivers by healthcare staff in both primary care centres and ADCCs has also been described as an important factor in adapting to these types of services (Davison et al., 2019) since it seems important to provide information that can break down barriers and help caregivers find the right time to attend ADCCs (Phillipson & Jones, 2012). Nursing professionals have an important role in this process due to the fact of having a unique position to provide supportive interventions to caregivers (Becque et al., 2020).…”
Section: Introductionmentioning
confidence: 99%